Seeding of breast cancer cell line (MDA-MB-231LUC+) to the mandible induces overexpression of substance P and CGRP throughout the trigeminal ganglion and widespread peripheral sensory neuropathy throughout all three of its divisions - Gutierrez, Silvia; Eisenach, James C; Boada, M Danilo (Molecular pain, 2021)
Some types of cancer are commonly associated with intense pain even at the early stages of the disease. The mandible is particularly vulnerable to metastasis from breast cancer, and this process has been studied using a bioluminescent human breast cancer cell line (MDA-MB-231LUC+). Using this cell line and anatomic and neurophysiologic methods in the trigeminal ganglion (TG), we examined the impact of cancer seeding in the mandible on behavioral evidence of hypersensitivity and on trigeminal sensory neurons. Growth of cancer cells seeded to the mandible after arterial injection of the breast cancer cell line in Foxn1 animals (allogeneic model) induced behavioral hypersensitivity to mechanical stimulation of the whisker pad and desensitization of tactile and sensitization of nociceptive mechanically sensitive afferents. These changes were not restricted to the site of metastasis but extended to sensory afferents in all three divisions of the TG, accompanied by widespread overexpression of substance P and CGRP in neurons through the ganglion. Subcutaneous injection of supernatant from the MDA-MB-231LUC+ cell culture in normal animals mimicked some of the changes in mechanically responsive afferents observed with mandibular metastasis. We conclude that released products from these cancer cells in the mandible are critical for the development of cancer-induced pain and that the overall response of the system greatly surpasses these local effects, consistent with the widespread distribution of pain in patients. The mechanisms of neuronal plasticity likely occur in the TG itself and are not restricted to afferents exposed to the metastatic cancer microenvironment.